High Performance LqGuid Chromatography of Carbohydrates - Sirimanne, V.D.P. (My University, 2016)
Attached

Carbohydrates as a group are of high importance, considered from both the practical and theoretical aspects. The different types of polysaccharides linked by glycosidic bonds, account for the different solubility, reactivity and appearance of the vast range of carbohydrates, which occur in living organisms. The behaviour of partially methylated sugars and methylated glycosides were studied in hplc using different columns and different solvent systemso The information thus obtained was used to investigate the structures of unknown carbohydrateso The results sllow that hplc is useful in the methylation analysis of polysaccharides, and for the preparation of reference compounds. Study of the formation of methyl glycosides showed that hplc is useful for the preparation of many methyl glycosideso Rates of glycosidation could be followed and op~imum conditions determined for the formation of a particular glycoside. The method is also applicable to the synthesis of the methyl glycosides of disaccharides, as shown by the isolation of the methyl glycosides of maltose. The glycoside work was extended to the compositional analysis of polysaccharideso Glycosides formed during methanolysis of polysaccharides were separated and quantitatively estimated. Successful separation of oligosaccharide series up to DP 8-9 # was achieved. Oligomers of the same DP but from different structural series e.g. the maltose and isomaltose series, had different retention times, showing that the separation mechanism operating was structure dependento